Development of a quantitative colorimetric LAMP assay for fast and targeted molecular detection of the invasive lionfish Pterois miles from environmental DNA - Hartle-Mougiou, Katherine; Gubili, Chrysoula; Xanthopoulou, Panagiota; Kasapidis, Panagiotis; Valiadi, Martha; Gizeli, Electra (Frontiers in Marine Science, 2024)
The Mediterranean basin has faced an increased influx of invasive species since the Suez Canal expansion in 2015. The invasive lionfish species, Pterois miles, has rapidly established new populations in the Eastern Mediterranean Sea, impacting local fish biodiversity. Here, we have developed a new, fast (< 35 min) molecular approach to detect and quantify P. miles environmental DNA (eDNA) in combination with a portable device for field-based analysis. Using a species-specific real-time colorimetric loop-mediated isothermal amplification (qcLAMP) for the cytochrome oxidase subunit 1 (COI) gene, we demonstrate a high sensitivity with a limit of detection of 0.002 ng DNA per reaction, equivalent to only 50 copies of the COI gene. The assay is specific to the target in the presence of closely related and co-occurring species, and it is quantitative over five orders of magnitude. We validated the assay using aquarium water samples and further demonstrated its utility on natural eDNA samples collected from locations around the island of Crete where P. miles had been sighted. P. miles was indeed detected in three out of nine locations, two nature reserves and a closed bay. Lack of detection in the remaining locations suggests that populations are still at a low density. We also demonstrate the feasibility of P. miles eDNA qualitative detection directly from the filter used to collect eDNA-containing particles, completely omitting DNA extraction. Overall, we present a new approach for fast and targeted eDNA quantification. The developed LAMP assay together, with the quantitative real-time colorimetric detection approach, open new possibilities for monitoring invasive P. miles in the field.